Transparent Exopolymeric Particles (TEP) Selectively Increase Biogenic Silica Dissolution From Fossil Diatoms as Compared to Fresh Diatoms - Toullec, Jordan; Moriceau, Brivaëla (Frontiers in Marine Science, 2018)
Diatom production is mainly supported by the dissolution of biogenic silica (bSiO2) within the first 200 m of the water column. The upper oceanic layer is enriched in dissolved and/or colloidal organic matter, such as exopolymeric polysaccharides (EPS) and transparent exopolymeric particles (TEP) excreted by phytoplankton in large amounts, especially at the end of a bloom. In this study we explored for the first time the direct influence of TEP-enriched diatom excretions on bSiO2 dissolution. Twelve dissolution experiments on fresh and fossil diatom frustules were carried out on seawater containing different concentrations of TEP extracted from diatom cultures. Fresh diatom frustules were cleaned from the organic matter by low ash temperature, and fossil diatoms were made from diatomite powder. Results confirm that newly formed bSiO2 dissolved at a faster rate than fossil diatoms due to a lower aluminum (Al) content. Diatom excretions have no effect on the dissolution of the newly formed bSiO2 from Chaetoceros muelleri. Reversely, the diatomite specific dissolution rate constant and solubility of the bSiO2 were positively correlated to TEP concentrations, suggesting that diatom excretion may provide an alternative source of dSi when limitations arise.